A current update on the phytopharmacological aspects of Houttuynia cordata Thunb - Kumar, Manish; Prasad, Satyendra K.; Hemalatha, S. (Pharmacognosy Reviews)
The present review is an attempt to put an insight into a medicinal plant Houttuynia cordata Thunb, which is indigenous to North‑East India and China. It is an aromatic medicinal herb belonging to family Saururaceae and is restricted to specialized moist habitats. The review provides detailed information regarding the morphology, distribution, phytochemistry, ethnopharmacological uses and also describes various pharmacological activities reported on the plant H. cordata. The review describes therapeutic efficacy of the whole plant and its extracts, fractions and isolated compounds in different diseased condition. Among the important pharmacological activities reported includes, anti‑mutagenic, anti‑cancer, adjuvanticity, anti‑obesity, hepatoprotective, anti‑viral, anti‑bacterial, anti‑inflammatory, free radical scavenging, anti‑microbial, anti‑allergic, anti‑leukemic, chronic sinusitis and nasal polyps activities. Thus, the present review will act as a source of referential information to researchers to perform clinical studies on isolated compounds that may serve the society and will help in improving human health care system.
Keywords: Anti‑viral; aristolactams; Houttuynia cordata; Saururaceae